Janus Kinase Inhibitors in the Treatment of Vitiligo: A Review - Qi, Fei; Liu, Fang; Gao, Ling (Frontiers in Immunology, 2021)
Vitiligo is a multifactorial reversible skin disorder characterized by distinct white patches that result from melanocyte destruction. Activated CXCR3+ CD8+ T cells promote melanocyte detachment and apoptosis through interferon-gamma (IFN-γ) secretion and chemokines secreted by keratinocytes through the Janus kinase (JAK)/signal transducer and activator of transcription (STAT)-1 signaling pathway results in further recruitment of CXCR3+ CD8+ T cells and the formation of a positive-feedback loop. JAK inhibitors target the JAK/STAT pathway and are now approved to treat many immune-related diseases. In the treatment of vitiligo, JAK inhibitors, including ruxolitinib, baricitinib, and tofacitinib, are effective, supporting the implication of the IFN-γ-chemokine signaling axis in the pathogenesis of vitiligo. However, more studies are required to determine the ideal dosage of JAK inhibitors for the treatment of vitiligo, and to identify other inflammatory pathways that may be implicated in the pathogenesis of this condition.